Biocompatible fluorenylphthalocyanines for one- and two-photon photodynamic therapy and fluorescence imaging. (January 2022) - Abid, Seifallah; Nguyen, Christophe; Daurat, Morgane; Durand, Denis; Jamoussi, Bassem; Blanchard-Desce, Mireille; Gary-Bobo, Magali; Mongin, Olivier; Paul-Roth, Christine O.; Paul, Frédéric
Abstract: The synthesis and the optical properties of a family of new fluorenyl phthalocyanines substituted with water-solubilizing triethyleneglycol chains is described. These biocompatible molecules exhibit strong one- and two-photon absorptions, together with fluorescence and photosensitization properties similar to those of their lipophilic analogues, thus outperforming unsubstituted zinc phthalocyanine in terms of brightness and singlet oxygen production. They were subsequently probed in vitro on cancer cells under one and two-photon excitation in both fluorescence imaging and photodynamic therapy experiments. The metal-free compound was shown to be more biocompatible and thus more promising than the zinc complex for theranostic applications. Highlights: Synthesis of two water-soluble phthalocyanines: free base & Zn(II) complex. New photosensitizers for theranostics. Tested in vitro on breast cancer cells (MCF-7). Allow fluorescence bioimaging and photodynamic therapy (PDT). The free-base was shown to be more biocompatible than the Zn(II) complex.